PENGARUH CGPI DAN BUSINESS MODEL TERHADAP FIRM PERFORMANCE DENGAN VALUE CREATION SEBAGAI VARIABEL MODERASI - Totok Dewayanto; Yuliati . . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
The aim of this research is to examine the impact of some variable on firm performance, which are: 1) the impact of CGPI on firm performance; 2) the impact of business model on firm performance; and 3) value creation as moderation variable in influence of business model on firm performance. The population of this research is all company that followed CGPI ranking listed on the Indonesia Stock Exchange in the period 2014-2018. The sample is selected using purposive sampling method and acquired 85 firms. The technique of analysis used for examining the hypothesis is OLS Regression analysis. The result showed that CGPI and Size doesn’t affect firm performance, business models affect firm performance positively. Meanwhile, value creation positively affect the association between business model and firm performance.